Math achievement is important, but task values are critical, too: examining the intellectual and motivational factors leading to gender disparities in STEM careers - Wang, Ming-Te; Degol, Jessica; Ye, Feifei (Frontiers in Psychology, 2015)
Although young women now obtain higher course grades in math than boys and are just as likely to be enrolled in advanced math courses in high school, females continue to be underrepresented in some STEM occupations. This study drew on expectancy-value theory to assess (1) which intellectual and motivational factors in high school predict gender differences in career choices and (2) whether students’ motivational beliefs mediated the pathway of gender on STEM career via math achievement by using a national longitudinal sample in the United States. We found that math achievement in twelfth grade mediated the association between gender and attainment of a STEM career by the early to mid-thirties. However, math achievement was not the only factor distinguishing gender differences in STEM occupations. Even though math achievement explained career differences between men and women, math task value partially explained the gender differences in STEM career attainment that were attributed to math achievement. The identification of potential factors of women’s underrepresentation in STEM will enhance our ability to design intervention programs that are optimally tailored to female needs to impact STEM achievement and occupational choices.